1,1′,2,2′-Tetramethyl-3,3′-(p-phenylenedimethylene)diimidazol-1-ium bis[bis(trifluoromethylsulfonyl)imide] - Abdul Rahim, Munirah Sufiyah (International Union of Crystallography, 2010)
The cation of the imidazolium-based ionic-liquid title salt, C(16)H(24)N(4) (2+)·2C(2)F(6)NO(4)S(2) (−), lies on a center of inversion; in the cation, the five-membered imidazolium ring is aligned at 84.4 (1)° with respect to the phenylene ring; the angle at the methylene C atom is 113.0 (2)°. In the anion, the negative charge formally resides on the two-coordinate N atom; the S—N—S angle at this atom is 125.2 (1)°.